Writer Sujatha and Cinema - Raguram, S. (My University, 2008)
Sujatha is often described as a multimedia writer rather than a writer and he was a multi-dimensional personality who proved his capability in many areas including short stories, novels, articles, cinema and online. The entry of Sujatha into the Tamil literature created an all-new wave. There would be no second opinion on the fact that Sujatha’s multi-talent, scientific background, reality and liveliness in his writings helped to enrich the Tamil cinema sphere. Some of his creations for Tamil cinema were unable to attain the commercial success they deserve. Even though there were possibilities to visualize his writings without compromising richness, as the cinema considered as the medium of directors, sometimes they were unable to find appropriate ways to implement this visualization. One of the primary reasons Sujatha’s viewers were able to comprehend his writings was the visual presentation of language by Sujatha; this attracted the minds of readers easily. His writings, barring a few, were either expressed in commercial settings or were not having sufficient depths as far as his cinema writings are concerned. Due to this reason, he was unable to stamp his uniqueness in the work carried out for cinema. He mostly works with a few persons in the cinema world including Actor Kamalhasan and Directors Maniratnam and Shankar. So his functioning in the cinema world is restricted to a small circle only. Inevitably, this small circle is also viewed from an alternative perspective.
Keywords: Multimedia; Writer; Tamil Cinema